Genetic Causes, Clinical Manifestations and Diagnosis of Central Nervous System Malformations with Emphasis on Corpus Callosum - Alomrani, Basmah; Javed, Murid; Mohammed Ali , Hani S. H.; Abo-Aba, Salah E. M.; AlBakheet, Albandary; Alqudairy, Hanan; Kaya, Namik (Journal of Contemporary Medical Sciences, 2022)
The pathological processes of the central nervous system, intrinsic or extrinsic, occurring during the embryonic period are the most common cause of pregnancy termination. The defects of the neural tube which is primitive form of brain and spinal cord are the most common central nervous system (CNS) malformations. In some defects the fetus continues to develop and results in the birth of a child with sever mental and physical deficiencies. The corpus callosum is the largest white matter tract connecting the two cerebral hemispheres and permits the transfer of information between the two cerebral hemispheres. Its partial or complete agenesis is caused by abnormalities during embryonic development. The severity of symptoms varies widely depending on the degree of dysgenesis. Hypotonia, visual impairment, seizures, spasticity, motor co-ordination issues, and atypical facial features are common symptoms. In this review we focus on genetic causes, clinical manifestations and diagnosis of various malformations of central nervous system with special emphasis on Corpus Callosum.